2013
DOI: 10.1371/journal.pbio.1001504
|View full text |Cite
|
Sign up to set email alerts
|

Neuroaesthetics and the Trouble with Beauty

Abstract: Neuroscience is increasingly being called upon to address issues within the humanities. We discuss challenges that arise, relating to art and beauty, and provide ideas for a way forward.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 39 publications
3
51
0
3
Order By: Relevance
“…Given the high reliability of face IP, even when estimated conservatively (via an alternate forms test-retest procedure), we conclude that the contribution of unshared environmental factors to face IP cannot be explained by unreliable measurement. Instead, our findings support the notion that individual aesthetic face preferences are truly shaped primarily by individual life experiences [20, 21]. …”
Section: Resultssupporting
confidence: 79%
“…Given the high reliability of face IP, even when estimated conservatively (via an alternate forms test-retest procedure), we conclude that the contribution of unshared environmental factors to face IP cannot be explained by unreliable measurement. Instead, our findings support the notion that individual aesthetic face preferences are truly shaped primarily by individual life experiences [20, 21]. …”
Section: Resultssupporting
confidence: 79%
“…Neuroaesthetic studies have revealed that when paintings are presented to observers they induce different patterns of activity in the brain depending whether they are considered beautiful or otherwise unappealing (Ishizu & Zeki, 2011, Kawabata & Zeki, 2004. The properties of the paintings underlying this brain activity are, however, unclear (Conway & Rehding, 2013). One reasonable hypothesis that has been considered is that the aesthetic value of paintings depends on the extent to which they mimic natural image statistics (Fernandez & Wilkins, 2008, Graham & Redies, 2010.…”
mentioning
confidence: 99%
“…The main objective of neuroaesthetics is to characterize the neurobiological foundations and evolutionary history of the cognitive and affective processes involved in aesthetic experiences and artistic and other creative activities [31]. Interest in the field of neuroaesthetics has grown remarkably during the last years.…”
Section: Modeling Esthetics Perception Of Visual Artsmentioning
confidence: 99%